Downregulation of miRNA-451a Promotes the Differentiation of CD4+ T Cells towards Th2 Cells by Upregulating ETS1 in Childhood Asthma - Tianyue Wang; Qianlan Zhou; Yunxiao Shang (Karger Publishers, 2020)
Children exposed to common aeroallergens may develop asthma that progresses into adulthood. Inflammation regulated by T helper 2 (Th2) cells, a specific subpopulation of CD4+ T lymphocytes, is involved in asthmatic injury. Herein, our microarray data indicated that microRNA-451a-5p (miRNA-451a) expression decreased by 4.6-fold and ETS proto-oncogene 1 (ETS1) increased by 2.2-fold in the peripheral blood lymphocytes isolated from asthmatic children (n = 4) as compared to control individuals (n = 4). The negative correlation between miRNA-451a and ETS1 was further validated in 40 CD4+ T cell samples (10 healthy vs. 30 asthmatic samples). In vitro, naïve CD4+ T cells isolated from control individuals were cultured under Th2 cell polarizing condition. miRNA-451a expression decreased while ETS1 increased in CD4+ T cells in the setting of Th2 cell polarization. Moreover, miRNA-451a knockdown enhanced Th2 cell polarization - cells positive for both GATA3 (GATA binding protein 3, a Th2-transcription factor) and CD4 increased, and the generation of Th2 cell cytokines, interleukin (IL)5 and IL13, increased. In contrast, miRNA-451a overexpression inhibited Th2 cell differentiation. Interestingly, dual-Luciferase assay proved ETS1 as a novel target of miRNA-451a. Moreover, enforced expression of ETS1 partially restored miRNA-451a-induced inhibition of IL5 and IL13, and increased the GATA3+CD4+ cell population. Collectively, our work demonstrates that downregulation of miRNA-451a upregulates ETS1 expression in CD4+ T cells, which may contribute to Th2 cell differentiation in pediatric asthma.